Rift Valley fever spreading by cattle movements: modelling of the viral circulation in a temperate and mountainous ecosystem of Madagascar - (:unkn) unknown (My University, 2013)
Rift Valley fever (RVF) is a zoonotic disease first described in 1930 in Kenya. Primarily transmitted between ruminant by mosquitoes of Aedes, Culex and Anopheles genus, it can also be transmitted to humans by direct contact with abortion products or body fluids of viraemic animals. This disease has been described in many African countries, in the Arabian Peninsula and the Indian Ocean. The circulation of RVF virus (RVFV) has been reported in three ecosystems: (i) semi-arid areas of South and East Africa, (ii) temporary ponds in arid areas, (iii) irrigated areas near large rivers. Within each of these ecosystems, the role of animal movements in the introduction of RVFV and that of mosquitoes in virus transmission has been strongly emphasized. Despite the existence of statistical models that predict the emergence of RVFV in East Africa based on rainfall level, the transmission mechanisms involved in other areas are still uncertain. The occurrence of an outbreak in a temperate and mountainous ecosystem of Madagascar, where the species and vector abundances are unfavorable to the persistence of RVFV, raises questions about these mechanisms.The objective of this thesis is to identify the factors and the epidemiological processes that support the RVFV recurrent circulation in a temperate ecosystem of Madagascar. The study took into account the socio-economic practices as well as major mosquito vectors of the area. The main modes of virus spread between cattle were studied during a three years serological follow-up. A mathematical model was elaborated and calibrated using empirical and field data collected in the area. Two cattle exchange practices could be distinguished: the usual trade and a traditional practice of barter. The results of the analysis suggest a different impact of these two practices in RVFV circulation. While trade may allow virus introduction, the barter practice would support its spread within the area. A deterministic model was built to
Keywords: African Research